Modernization of Hospital Management in Health Care Institutions - Vásquez Sáenz, Oscar Augusto (2023)
A brief review was carried out with a theoretical approach to the current hospital organization and its modernization. An approach of the current hospital organization is shown. In addition, the procedure and the particularities of the directions of the hospital sector are presented; Being able to later analyze the mechanisms of modernization to entities related to the well-being of the population and to be able to make optimal use of management methodologies. The factors that motivate the change, because they are the most complicated organizations in their specific area; being so that its activities that vary in different sectors according to what is specified in its guidelines can be clearly understood, even when considering the peculiarities of each organization.